Occupational trajectories among refugees in Austria: The role of co-ethnic and austrian social networks in job search - Sandra M. Leitner (The Vienna Institute for International Economic Studies (wiiw), 2023)
This paper analyses occupational trajectories of refugees from their last job in the home country to their first and current jobs in Austria and the role of co-ethnic and Austrian social networks in job search, using data from a large-scale survey of recognised refugees from Syria, Afghanistan, Iraq and Iran who have predominantly come to Austria since 2010, thereby covering the strong refugee wave of 2015-2016. The results corroborate a U-shaped pattern, with a sharp initial occupational loss followed by a rather moderate occupational recovery. Although native social networks play no role for occupational changes, co-ethnic social networks - particularly when used as a stand-alone job search strategy - prove detrimental along the entire trajectory. However, co-ethnic social networks are beneficial if used in combination with the Austrian labour market service or NGOs. Some refugees prove particularly vulnerable, such as older refugees or highly educated refugees who undergo more pronounced initial occupational downgrading, with subsequent occupational upgrading either limited or absent.
Keywords: J15; J24; J62; 330; Refugees; labour market integration; occupational trajectories; social capital